ASTROFOTOGRAFI NEBULA BERBASIS ZWO SEESTAR S50 DALAM PENGEMBANGAN PEMBELAJARAN ILMU FALAK - Muthmainna, Esa Aulia; Syarif, Muh. Rasywan (HISABUNA: Jurnal Ilmu Falak, 2026)
Abstract This study aims to analyze the implementation of astrophotography using the ZWO Seestar S50 with nebula objects in the development of Astronomy learning. The sub-questions examined include: (1) the implementation of astrophotography using the ZWO Seestar S50 with nebula objects in Astronomy learning, and (2) the role of nebulae as astrophotography subjects in supporting the development of Astronomy learning. This study uses a descriptive qualitative method. Data was obtained through direct observation of nebula objects using the ZWO Seestar S50 and documentation of the observation results. The collected data were then analyzed descriptively through the stages of data collection, processing, and interpretation. Research results show that the implementation of astrophotography using the ZWO Seestar S50 in astronomy learning is carried out through stages of instrument introduction, observation preparation, image capturing, nebula image processing, and the use of observation results as learning media. In addition, nebulae serve as astrophotography study objects that support the development of astronomy learning because they can visualize astronomical phenomena in a tangible way and strengthen the integration between science and Islamic values. The implications of this research indicate that the use of smart telescope-based astrophotography can be an innovation in astronomy learning. Keywords: Astrophotography, Nebula, ZWO Seestar S50